Hydrocarbon Accumulation Mechanism of Ordovician in the Halahatang Area, Tarim Basin—Evidence From Organic Geochemistry - Huo, Fei; Wang, Xingzhi; Li, Luping; Luo, Xin; Yang, Xiyan; Shen, Chen; Li, Liang; Ruan, Yunbo; Huang, Huiwen (Frontiers in Earth Science, 2022)
As an important oil and gas bearing area in Tarim Basin, Halahatang area has great potential for resource exploration. However, the research on oil and gas sources and filling period of Lower Paleozoic Ordovician is still not deep enough. In this study, the organic geochemical analysis of source rocks, the simulation technology of hydrocarbon generation evolution basin, the distribution characteristics of fluid inclusions and the measurement of uniform temperature are used，and combined with the stable isotope of natural gas and the characteristics of oil-source biomarkers, and the process of oil and gas accumulation is restored. The results show that : ①Cambrian source rock is the main contributor to Ordovician crude oil in Halahatang area, and its crude oil shows the characteristics of light weight, rich chain hydrocarbon and poor aromatic hydrocarbon. The composition of C7 compound shows the advantage of n-heptane, which belongs to type I parent material. The biomarker compounds show the characteristics of high content of long-chain tricyclic terpane and high Ts / Tm value, and the crude oil is considered to be a highly mature sapropelic parent material source oil. ②The carbon isotopes of methane and ethane of Ordovician natural gas in Halahatang area are light, showing obvious characteristics of sapropelic gas.③There are three stages of oil and gas accumulation process in Ordovician reservoirs in Halahatang area. The middle and late Caledonian period reached the hydrocarbon generation threshold and began to generate oil. The late Hercynian period was the main accumulation period, and the Himalayan period was dominated by dry gas filling. ④The crude oil generated in the Middle-Late Caledonian study area migrated and accumulated along the faults and conductive layers to the high parts of the northern structure. The migration of oil and gas in the late Hercynian period was limited by the bitumen produced by early biodegradation. Since the asphalt plugging condensate gas has almost failed to cause gas invasion to the reservoir, the Ordovician reservoir still maintains the characteristics of crude oil associated gas, forming oil and gas reservoirs with gas caps.